(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Dal socialismo di Stato allo Stato confessionale - 2. L’Accordo di collaborazione con l’Esarcato della Chiesa ortodossa Russa in Bielorussia - 3. Le materie oggetto di accordo e la confessionalizzazione delle istituzioni e dello Stato - 4. Gli accordi con gli altri culti tradizionali - 5. Il prezzo dell’alleanza: la lotta alle nuove confessioni religiose attraverso la legge sulla libertà religiosa - 6. Alcune considerazioni finali. Belarus in search of its identity and the process of confessionalisation of the State ABSTRACT: The current piece analyzes the stages characterizing the transition from State socialism to State Confessionalism through the Collaboration Agreement between the Belorussian Government and the Exarcate of the Russian Orthodox Church in Belarus. The main subjects of the agreement and the confessionalisation process of the institutions are taken into account. The essay deals with the alteration of the basic functions of the Belorussian State, namely education, health services and assistancy to the segregating foundations, etc. Furthermore, the agreements with other traditional religious groups are relevant. In this regard, the law on religious freedom is mainly used to resist the spread of such new cults. The study is then finalized to highlight the existing link between the Russian Orthodox Church traditions and cultural heritage with the estabilishment of a national identity. This symbolic bond is then used to build the basis of a new State with strong religious features in sensitive matters such as the control over births, bridal affairs, cultural and social valuesin a nationalist and sovereignist key.